PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN TERHADAP RISIKO SISTEMATIS (BETA) SAHAM PERUSAHAAN MANUFAKTUR (STUDI PADA BURSA EFEK INDONESIA, 2005 â 2009) - , Riswandi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research with the title of the influence of fundamental factors on the company's systematic risk (beta) of manufacturing categories (Study on the Indonesia Stock Exchange, 2005-2009) aimed to test the effect of dividend payout ratio (DPR), Liquidity Ratio (LIQUID), firm size (SIZE), debt to Asset Ratio (DAR), Earning Variability (EVAR), Price Earning Ratio (PER) and Price Book Value (PBV) of the systematic risk (beta) shares. Tests conducted using panel data regression analysis. Significance test model was chosen to model fixed-effect model produces the best estimate. Based on the results of regression analysis is known that the variable dividend payout ratio (DPR), firm size (SIZE), Debt to Asset Ratio (DAR), Price Earning Ratio (PER) and Price Book Value (PBV) significantly influence the systematic risk (beta) stock, while the variable Liquidity Ratio (LIQUID) and Earning Variability no significant effect on systematic risk (beta). Taken together all the variables in the model significantly influence the systematic risk (beta). This is indicated by the F-statistic value of 6,6093 and Prob (F-statistic) 0.0000 significant with alpha 1 percent. Independent variables in the model is able to explain the dependent variable (beta) amounting to 66.16 percent.